Quality Of Service And Emotional Bonding To Increase Furniture Sales - Ifan Sri Cahyani Marunduri; Elfitra Desy Surya; Erwansyah (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the influence of service quality and emotional bonds to increase sales at Gunawan Perabot. The research is a creative research using data processing with SPSS version 22. In this study, a population of 180 respondents was used, then using the Slovin formula, a sample of 64 respondents was obtained. The data sources used are primary data and secondary data. The data collection technique uses questionnaires, observations, and interviews. The data analysis techniques are multiple linear regression, classical assumption test and hypothesis test. The results of the study show that the quality of service has a positive and significant effect on increasing sales at Gunawan Furniture. Emotional bonds have a positive and significant effect on the increase in sales at Gunawan Furniture. The quality of service and emotional bonds have a positive and significant effect on the increase in sales at Gunawan Furniture. There is a strong correlation between product quality, service quality, and emotional bond with customer satisfaction of 55.1% and the remaining 44.9% can be explained by other variables that are not researched such as promotion, distribution, marketing communication, and so on. In the study, it is recommended to improve the quality of service and emotional bonds so that furniture sales become better and liked by consumers.